Attack of the tighty whities! - Krulik, Nancy E.; Blecha, Aaron (New York : Grosset & Dunlap, 2012)
George is representing his school at the county-wide spelling bee, and hopes to compete without getting overpowered by an embarrassing, magic super burp.
Accelerated Reader AR
Keywords: Conduct of life -- Juvenile fiction; Belching -- Juvenile fiction; Spelling bees -- Juvenile fiction; Schools -- Juvenile fiction; Magic -- Juvenile fiction; Behavior -- Fiction; Belching -- Fiction; Spelling bees -- Fiction; Schools -- Fiction; Magic -- Fiction